The phenomenology of auditory verbal hallucinations in schizophrenia and the challenge from pseudohallucinations - López-Silva, Pablo; Cavieres, Álvaro; Humpston, Clara (Frontiers in Psychiatry, 2022)
In trying to make sense of the extensive phenomenological variation of the first-personal reports on auditory verbal hallucinations, the concept of pseudohallucination is originally introduced to designate any hallucinatory-like phenomena not exhibiting some of the paradigmatic features of ‘genuine’ hallucinations. After its introduction, Karl Jaspers locates the notion of pseudohallucinations into the auditory domain appealing to a distinction between hallucinatory voices heard within the subjective inner space (pseudohallucination) and voices heard in the outer external space (real hallucinations) with differences in their sensory richness. Jaspers’ characterization of the term has been the target of a number of phenomenological, conceptual and empirically-based criticisms. From this latter point of view, it has been claimed that the concept cannot capture distinct phenomena at the neurobiological level. Over the last years, the notion of pseudohallucination seems to be falling into disuse as not major diagnostic system seems to refer to it. In this paper, we propose that even if the concept of pseudohallucination is not helpful to differentiate distinct phenomena at the neurobiological level, the inner/outer distinction highlighted by Jaspers’ characterization of the term still remains an open explanatory challenge for dominant theories about the neurocognitive origin of auditory verbal hallucinations. We call this, ‘the challenge from pseudohallucinations’. After exploring this issue in detail, we propose some phenomenological, conceptual, and empirical paths for future research that might help to build up a a more contextualized and dynamic view of auditory verbal hallucinatory phenomena.